Water-Sensitive Urban Design in Istanbul: An Ecological Corridor Framework from the Ömerli Basin to the Tuzla Coastal Zone - Buzghia, Raana M O; Dizdaroğlu, Didem (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2026)
Water-related hazards in urban environments are intensifying due to rapid urbanization and climate change, with flash-flood risks increasingly evident in Istanbul. Conventional gray infrastructure alone cannot adequately address the interconnected hydrological and ecological pressures affecting metropolitan landscapes. This study develops a GIS-based Water-Sensitive Urban Design (WSUD) framework for the Ömerli Basin–Tuzla corridor, integrating flood vulnerability assessment, urban pressure evaluation, and ecological connectivity modeling through multi-criteria evaluation and the Minimum Cumulative Resistance model. The analysis identifies spatial conflict zones where flood exposure, urban development pressure, and ecological fragmentation converge, revealing a pronounced north–south gradient across the corridor. Based on these findings, a corridor-scale blue–green infrastructure framework is proposed to guide targeted nature-based interventions. The study contributes to metropolitan scale WSUD research by demonstrating how integrated territorial analysis can support spatially differentiated planning and climate-resilient urban development in rapidly urbanizing coastal regions.